Transnational Identity in Indra Bahadur Rai’s Selected Short Stories - Timalsina, Ramji (Prithvi Academic Journal, 2020)
Are the people of Nepali origin who are born in India and live there transnational? This is a piercing question in transnational discourses in Nepal and India these days. But its answer is clear once we take the help of the concept of transnationalism: they are transnational Nepalis living in India. This reality is further clarified with the studies on Indra Bahadur Rai’s short stories. Almost all the characters in his stories are the people of Nepali origin living in Darjeeling. They are unhappy there and always behave like the temporary residents of the place. Most of his stories deal with the life of these people in relation with their search for the origin and related physical and psychological journeys. Even the images, symbols and settings used in the stories connect themselves with the idea of journey and the problems of settlements. This article deals with the same aspects of his collection of stories entitled Pratinidhi Kathaa [Representative Stories]. The stories are analyzed with the help of interpretive methodology and use of Steven Vertovec and Jenine Dahinden’s ideas of transnationalism. John McLeod, Rebecca L. Walkowitz, Roland Végső and Winfried Fluck’s ideas of transnational literature are used as the basic concepts in analysis.